Impact of knowledge workers characteristics in promoting organizational creativity: An applied study in a sample of Smart organizations - Abbas G. Atiyah, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to test the effect of knowledge workers in enhancing the level of organizational creativity. For this purpose, the hypothesis of the research was developed and field-tested. The study sample included (194) managers and sub-managers in Asiacell company, and the researcher used the questionnaire in collecting data and he analyzed it statistically by using the (SPSS V.23) program. Accordingly, he recommended a number of recommendations, the most important of which is giving the highest importance to knowledge workers in the organization because of their great role in smart organizations.